New approaches in teaching english to students of automobile specialties - Ponikarovska, Svitlana; Понікаровська, Світлана Володимирівна; Поникаровская, Светлана Владимировна (Харківський національний автомобільно-дорожній університет, 2019)
New approaches in teaching foreign language, especially English as the language of international communication and the most common language in the internet space are the issue of many discussions and researches. Computers and telecommunications that are reshaping higher education, alter the daily operations and expand the missions and opportunities of universities, become the integral part of the teaching process. The students of engineering higher schools, especially future automobile engineers because they are at the cutting edge of modern industry, and, consequently, must be aware of new developments and be able to cooperate with foreign partners, require the combination of traditional and computer-assisted cooperative language learning which provides a space in which the facilitation of learning can take place. However, application of new technologies must be an assisting instrument, but not a self-inclusive tool. The task of a teacher is to be an integral part of the process, not an operator of the computer. Cultivation of students’ capacity of thinking should be the major objective in teaching today. Goal. The goal of the article is proving that the education sector is no exception in our fast developing society. The nature of its target audience – mostly young and highly connected – means that the sector must adapt to the new requirements, which means computer literacy and friendly atmosphere with the main task of facilitating learning. Methodology. Methods of analysis, research and development of new solution were used. Results. In the result of the analysis it was proven that new technologies together with new attitude bring a desired result in teaching foreign language in today’s reality. Originality. Suggestions for using new technologies in the classroom as well as the ways to maintain working atmosphere with friendly communication are made, including the rapport among students themselves. Practical Value. The practical value of the work can be the ideas for improving development of the lesson, using gadgets for combination of individual work and consequent communication, prevention for a teacher from becoming just an assistant of technologies in the process of teaching.
Нові підходи у викладанні англійської мови студентам автомобільних спеціальностей
Новые подходы к преподаванию английского языка студентам автомобильных специальностей
Keywords: atmosphere; communication; technology; knowledge; learning; interactive; атмосфера; спілкування; технологія; знання; навчання; інтерактивний; общение; технология; знания; обучение; интерактивный; 378.14; 10.30977/VEIT.2019.16.0.43